Leaflet-Based Balanced Nutrition Education to Support Healthy Eating Habits for Eighth Grade Students at SMP Negeri 31 Medan Tuntungan (JURNAL PENGMAS KESTRA (JPK), 2025)
Adolescence is a critical stage of life characterized by rapid physical and psychological growth, which requires adequate and balanced nutritional intake. However, limited nutrition knowledge often leads adolescents to adopt unhealthy eating habits, such as frequent consumption of fast food, sugary beverages, and low intake of fruits and vegetables. This community service activity aimed to improve balanced nutrition knowledge and support the adoption of healthy eating habits among eighth-grade students through leaflet-based nutrition education. The activity was conducted in December 2025 at UPT SMP Negeri 31 Medan Tuntungan using a descriptive qualitative approach with a cross-sectional design. A total of 72 male and female students participated in the program. The educational intervention was delivered through interactive lectures, discussions, and the distribution of leaflets containing information on balanced nutrition principles, portion control, dietary diversity, and the limitation of foods high in sugar, salt, and fat. The results demonstrated a significant improvement in students’ knowledge and understanding of balanced nutrition after the educational intervention. The proportion of students with good nutrition knowledge increased substantially, along with improvements in understanding healthy eating patterns and awareness of limiting high-calorie food consumption. Furthermore, students showed positive attitudes toward improving their daily eating habits. Leaflet media were considered effective because they are informative, attractive, easy to understand, and suitable for independent learning. In conclusion, balanced nutrition education using leaflet media is effective in enhancing adolescents’ nutrition knowledge and fostering positive attitudes toward the implementation of healthy eating habits.